2015
DOI: 10.4293/jsls.2013.00401
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Loss of a Surgical Needle: A Laparoscopic Dilemma

Abstract: Background:Increasing awareness around patient safety and efforts to reduce medical errors has become a priority in the modern health care system. Losing needles during laparoscopic procedures is an uncommon occurrence; however, it poses a significant dilemma for the operating surgeon because retrieval can be a major challenge even for highly skilled and experienced operators.Objective:The objective of this paper was to review the current literature and highlight this potentially serious issue and suggest a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…With the increasing use of minimally invasive surgical (MIS) techniques, there has been an expected increase in RSIs associated with MIS as compared to open procedures [ 12 ]. Risk factors associated with MIS include a limited field of view and the lack of tactile feedback for the operator [ 12 , 17 , 22 ] which make it more difficult to locate a lost object and therefore increase the risk of an RSI event [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increasing use of minimally invasive surgical (MIS) techniques, there has been an expected increase in RSIs associated with MIS as compared to open procedures [ 12 ]. Risk factors associated with MIS include a limited field of view and the lack of tactile feedback for the operator [ 12 , 17 , 22 ] which make it more difficult to locate a lost object and therefore increase the risk of an RSI event [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Local reactions to RSIs can be inflammatory and exudative resulting in abscesses, fistulas, obstructions, or erosions into nearby structures [24,30,46,[61][62][63]. Reactions can also be aseptic, forming stable granulomas, the progression of which can bring to compression on nearby structures, causing chronic pain and irritation or other more significant symptoms [10,21,22,30,35,44,61]. Complications of RSIs have been described in a variety of case reports, and it has been shown that patients with known RSIs are twice as likely to have at least one post-operative complication, with morbidity of approximately 50% [2,30] and an extension of hospital stay in 59% up to 8 days [38].…”
Section: The Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…After initial survey does not reveal the needle, they recommend the use of an intraoperative magnetic needle retriever which is a reliable and rapid method for recovery. 21…”
Section: Discussionmentioning
confidence: 99%
“…Zaman and coworkers have recently noted that minimally invasive surgery using robotic systems, often with multiple bedside members and a large array of instruments, increases the chance of losing foreign bodies. 3 A missing foreign body is an unnerving event which prompts an active and exhaustive search, ideally performed in a systematic manner to increase the chances of identification and retrieval. Jayadevan and associates recently suggested a lost needle identification protocol that includes initial operative field survey, radiograph for needle >13 mm, port inspection, anatomically systematic visual search, and floor/table sweep.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%